Cultural-religious synergy in gender-responsive education: A qualitative study of the hukurila indigenous community in maluku - Feky Manuputty; Simona Christina Henderika Litaay; Afdhal; Nathalia Debby Makaruku (Balai Diklat Keagamaan Ambon, 2026)
This study investigates how cultural traditions and religious values intersect with gender-responsive education to shape family well-being in indigenous Maluku communities, focusing on Hukurila village in Ambon. While gender-responsive education is central to the Sustainable Development Goals (SDG 4: Quality Education and SDG 5: Gender Equality), patriarchal norms continue to limit women’s access to education, particularly in entrepreneurship and leadership, with minimal family engagement in promoting gender equity. The research addresses how cultural-religious synergy can support inclusive education in this context. Using a qualitative descriptive approach within the sociology of education and gender studies, data were collected through in-depth interviews with youth, women, customary leaders, religious leaders, and local authorities; participatory observation; and analysis of local documents and church programs. Thematic analysis explored how communities construct gender equality through cultural and religious frameworks. Findings reveal tensions between patriarchal traditions and gender agendas. The “tiga batutungku” (government, customary, and religious leaders) act ambivalently, while local wisdom, such as badraheng, offers potential for inclusive education. Church family programs further demonstrate the capacity to shift paradigms toward equitable family well-being. The novelty lies in advancing the concept of cultural-religious synergy as a framework for gender-responsive education in indigenous contexts.